Penerapan Metode Auditory Intellectualy Repetition (AIR) untuk Meningkatkan Hasil Belajar Siswa - Nadia Elga Saputri; Pipit Firmanti; Weni Anggraini (SOKO GURU: Jurnal Ilmu Pendidikan, 2023)
The quality of the learning process in the classroom is a determinant of student learning outcomes. Based on observations that teachers in the learning process use conventional learning models which occur more in the form of lectures and giving practice questions. So according to observations, student learning outcomes are still low and have not yet reached the completeness mark. Based on these observations, to improve student learning outcomes in the learning process using the Auditory Intellectual Repetition (AIR) method. Based on the advantages of using the Auditory Intellectual Repetition (AIR) method, namely students are trained to read mathematical concepts carefully, then write them back into notebooks using their own language, these activities can increase students' understanding of the concepts that have been taught. Based on the results students' learning after using the audiotory intellectually repetition method that out of 18 students in class VIII 1 MTs S Kamang Mudik 4 students got scores in the value interval 50≤x<70 which means low category, 2 students in the value interval 70≤x<80 which means t student were in the medium category, and 8 students scored in the value interval 80≤x<90, which means their score was in the high category, and 4 students who scored 90≤x≤100, which means they were in the very high category. After the average score the results 81 students' mathematics learning is converted into the 5 categories above, so the average mathematics learning outcomes for class VIII 1 MTs S YATI Kamang Mudik after being taught using the auditory intellectually repetition model is generally in the high category.